A school-based study of sexual health knowledge among sexually active adolescent girls in Calabar, Nigeria - Amosu, Ademola M.; Ajike, Saratu O.; Omoronyia, Ogban E.; Olaoye, Titilayo F. (International Journal Of Community Medicine And Public Health, 2022)
Background: There is high burden of sexually transmitted infections (STIs) and unwanted pregnancy among young people. In many developing countries including Nigeria, there is paucity of literature on sexual health knowledge among sexually active adolescent girls, as key vulnerable population. This study aimed at assessing level of sexual health knowledge among adolescent secondary school girls in Calabar, Nigeria. Methods: Cross-sectional study design was used, with recruitment of randomly selected sexually active adolescent girls in three public secondary schools in Calabar. Sexual health knowledge was assessed using structured, pre-tested questionnaire, knowledge scores were converted to percentage, and 50% or greater was considered satisfactory. Factors associated with level of knowledge was assessed using Chi-square test, with p value set at 0.05. Results: One hundred and eight (180) respondents were studied, with mean age of 17.4±1.2 years (14-19 years). Mean age at sexual debut was 15.0±2.1 years, ranging from 11 to 19 years. Mean knowledge score (out of maximum of 62) was 25.4±4.2 (9-49), corresponding to 41.0±7.8% (14.5 to 79.0%). Sixty respondents (33.3%) had satisfactory level of knowledge on sexual health. Higher level of paternal and maternal education, married parental status, were associated with satisfactory level of knowledge. Conclusions: There is suboptimal level of sexual health knowledge among sexually active school girls in Calabar. There is urgent need to provide sexual health educational interventions. The school-based family life HIV education (FLHE) program, should be revived, to mitigate sourcing of false sexual health information from peers.